2011
DOI: 10.1123/ijspp.6.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Muscle Activation in Power-and Endurance-Trained Boys

Abstract: Previous studies in adults have demonstrated power athletes as having greater muscle force and muscle activation than nonathletes. Findings on endurance athletes are scarce and inconsistent. No comparable data on child athletes exist.Purpose:This study compared peak torque (Tq), peak rate of torque development (RTD), and rate of muscle activation (EMG rise, Q30), in isometric knee extension (KE) and fexion (KF), in pre- and early-pubertal power- and endurance-trained boys vs minimally active nonathletes.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…Values are mean±SEM present study demonstrated that rapid muscle activation (RER), which may be affected by factors that include earlier motor unit recruitment, higher discharge rates, and/or higher rates of doublet discharge (Mitchell et al 2011), was not different between the young and old men (Fig. 4), which suggests that the age-related decrease in relative RTD is unaffected by the rate of activation of motor units.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Values are mean±SEM present study demonstrated that rapid muscle activation (RER), which may be affected by factors that include earlier motor unit recruitment, higher discharge rates, and/or higher rates of doublet discharge (Mitchell et al 2011), was not different between the young and old men (Fig. 4), which suggests that the age-related decrease in relative RTD is unaffected by the rate of activation of motor units.…”
Section: Discussionmentioning
confidence: 56%
“…2). The rate of EMG rise (RER; % PEMG s -1 ) was used to examine the rate of muscle activation (Clark et al 2011(Clark et al , 2013Mitchell et al 2011) and was calculated as the linear slope of the normalized EMG-time curve at time intervals of 30 ms (RER30), 50 ms (RER50), and 75 ms (RER75) from onset similar to the procedures described by Aagaard et al (2002) and Barry et al (2005). The specific time intervals for determining RER (in particular the selection of 75 ms instead of 100 ms) were used because of a characteristic decrease in the EMG signal amplitude occurring at~80-100 ms following the signal onset (Aagaard et al 2002; Note: RER time intervals do not correspond directly to the RFD intervals due to the electromechanical delay.).…”
Section: Electromyography Measurementsmentioning
confidence: 99%
“…Practically, this indicates that improvements in RFD in children may require specific training modalities. For example, rates of muscle activation appear to be greater for children involved in sports where muscle forces must be developed rapidly, such as gymnastics (33), indicating that basic strength or plyometric training may be beneficial for improving muscle activation in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we have shown both Q 30 and the rate of force development (RFD) to be significantly higher in young male gymnasts (typically trained for explosive muscular performance), than in young swimmers (mostly endurance-trained), or nonathletes (67). It may be argued that such differences reflect gymnasts' preselection rather than true training effect.…”
Section: Emg-derived Evidencementioning
confidence: 91%